Accuracy and variability in early spontaneous word production: The effects of age, frequency and neighbourhood density. Issue 2 (April 2020) - Jones, Samuel David
High rates of error and variability in early word production may signal speech sound disorder. However, there is little consensus regarding the degree of error and variability that may be expected in the typical range. Relatedly, while variables including child age, word frequency and word phonological neighbourhood density are associated with variance in word production accuracy and variability, such effects remain under-examined in spontaneous speech. This study measured the accuracy and variability of 234, 551 spontaneous word productions from five typically developing children in the Providence corpus (0;11–4;0). Using Bayesian regression, accuracy and variability rates were predicted by age, input frequency, phonological neighbourhood density, and interactions between these variables. Between 61% and 72% of word productions were both inaccurate and variable according to strict criteria. However loosening these criteria to accommodate production inconsistencies unlikely to be considered erroneous (e.g. the target /ælə ɡeɪtəɹ/ pronounced /ælɪ ɡeɪtəɹ/) reduced this figure to between 10% and 17%, with the majority of word productions then classed as accurate and stable (48%–58%). In addition, accuracy was higher and variability was lower in later months of sampling, and for high frequency words and high density words. The author discusses the implications of these results for future research and the differential diagnosis of speech sound disorder, and presents an explanatory account of findings emphasizing the development of oral-motor skills and increasingly detailed phonological word representations.